(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the decisive role of competence and professional skills in the field of language teaching, and shows the need for teachers not only to be competent in the language they teach, but also to have pedagogical skills. It is emphasized that the importance of advanced technologies and methods in the field of education, especially in language learning, is increasing, the differences in the concepts of competence and professionalism, meeting the established standards do not guarantee the full application of knowledge and skills. Emphasis is placed on the importance of information-analytical competence, particularly in language teaching, and the need for teachers to effectively analyze information. Various methods of language learning are explored with an emphasis on listening comprehension. The article also provides an overview and different types of competence.